Oral malodor-related parameters in the Chinese general population - Xue Nan Liu (Blackwell Synergy, 2006)
Objectives: To estimate the prevalence of halitosis in the Chinese population and to assess the relationships between halitosis and oral health, social and behavioural factors. Methods: The correlation between the incidence of oral malodor and oral health was surveyed in a sample of 2000 individuals (1000 males and 1000 females) aged 15–64 years residing in urban and rural areas. Malodor was measured with both organoleptic measurements and with a portable sulphide monitor. Assessment of oral health included decayed, missing and filled teeth (DMFT), periodontal status, dental plaque, and tongue coating. Behavioural and social factors related with oral health or halitosis were also investigated. Results: The prevalence of halitosis was 27.5% according to the organoleptic score. The level of volatile sulphur compounds (VSCs) in mouth air was significantly lower in males and in some of the age groups after lunch. Age and location of residence (rural or urban areas) did not influence the VSCs concentration in mouth air. The amount of tongue coating played the most important role in increasing VSCs concentration in mouth air, followed by periodontal status and plaque index values. DMFT, social, and behavioural factors did not contribute to halitosis. Conclusions: Tongue coating score, modified sulcus bleeding index and calculus index were factors significantly related to oral malodor in this study.